Leadership for inclusive academic integration: Perspectives on computer science curriculum design - Nacheva, Radka (Journal of Interdisciplinary Studies in Education, 2026)
Educational institutions should promote student entrepreneurship to foster personal growth, skill development, and social change. By employing collaborative learning strategies that develop leadership and entrepreneurial skills, teachers can improve this. In addition to introducing a business simulation-based learning approach to encourage academic motivation, leadership development, and creative thinking, this paper examines the importance of student leadership in computer science education. This approach, which emphasizes cooperation, was tested with 136 computer science students at a Bulgarian university. The results showed that teamwork and listening skills were more important to students than technical knowledge. The findings imply that business simulations provide a useful setting for developing the technical and leadership abilities essential to the technology industry.